The Cross-Talk Between Gut Microbiota and Lungs in Common Lung Diseases - Zhang, Dapeng; Li, Sha; Wang, Ning; Tan, Hor-Yue; Zhang, Zhimin; Feng, Yibin (Frontiers in Microbiology, 2020)
Emerging findings indicate there is a vital cross-talk between gut microbiota and the lungs, which is known as gut-lung axis. The gut disturbances in lung diseases including allergy, asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis and lung cancer were observed by extensive studies. Investigating how gut microbiota impact other distant organs is of great interest in recent years. Although it has not been fully understood whether the disturbance is the cause or effect of lung diseases, alterations in the gut microbial species and metabolites have been linked to changes in immune responses and inflammation as well as the disease development in the lungs. In this article, we systemically review the role and mechanisms underlying the changes in the constituent of gut microbiota and metabolites in lung diseases. In particular, the roles of gut-lung axis in mediating immune responses and reshaping inflammation are highlighted. Furthermore, we discuss the potential of strategies to manipulate the gut microbiota and metabolites as the therapeutic approach for lung diseases.